Testing practices in European countris: The proffesional' view - Muniz, Jose; Bartram, Dave; Evers, Arne Boben, Dusica; Matešić, Krunoslav (2001)
Background: Currently, different European institutions and international bodies are developing projects and actions aimed to improve testing practices. The European Federation of Professional Psychologists Associations (EFPPA) has created the Standing Committee on Tests and Testing to coordinate these activities. This committee, working with other international bodies such as the International Test Commission, has developed different activities in order to improve tests and testing in the EFPPA countries. Aims: The main goal of this project is to explore the opinions of professional psychologists on the current testing practices in five European countries (Croatia, Holland, Slovenia, Spain and the United Kingdon). We consider reliable information on practices obtained from professionals is essential as a first step to improve test use. Methods: A questionnaire of 35 items was developed by the EFPPA Standing Committee on Tests and Testing and mailed to the professionals of the five countries. Results: The rate of answers was very satisfactory in all five countries: Croatia (218), Holland (2, 079), Slovenia (321), Spain (3, 455) and United Kingdom (2, 407). Descriptive statistics for the 25 items of the questionnaire are presented and a list of those tests most frequently used is offered. Conclusions: In general, professional psychologists show a positive attitude toward tests and testing, revealing at the same time the need for institutions to adopt a more active role in promoting good practices. Tests most frequently used are personality and intelligence tests.
ENG